Effect of Radioiodine Treatment on Quality of Life in Patients with Subclinical Hyperthyroidism: A Prospective Controlled Study - Larisch, Rolf; Midgley, John E. M.; Dietrich, Johannes W.; Hoermann, Rudolf (Nuklearmedizin - NuclearMedicine, 2024)
Radioiodine treatment (RIT) has a high success rate in both the treatment of hyperthyroidism and improving the quality of life (QoL) of symptomatic patients. In asymptomatic patients with subclinical hyperthyroidism thyroid related QoL outcomes are less well known.Methods Study aim was to evaluate thyroid-related QoL in patients with subclinical hyperthyroidism mostly due to toxic nodular goitre undergoing RIT, compared to a control group of euthyroid subjects. Study design was monocentric, prospective, controlled. Fifty control subjects were enrolled and 51 RIT patients. Most subjects were examined at least twice at an interval of 6 months, with visits immediately before and 6 months after treatment in the RIT group. QoL was estimated with the ThyPRO questionnaire, using its composite scale as primary outcome. Treatment effect was the mean adjusted difference (MAD) between groups over time, using repeated? measures mixed? effects models.Results TSH concentrations were lower in the RIT group prior to treatment and recovered thereafter slightly above the level of the control group. Correspondingly, QoL improved significantly after 6 months from a worse level in the RIT group, compared to controls (MAD –10.3 [95% CI –14.9, –5.7], p<0.001). QoL improvements were strong for general items, but less pronounced for the hyperthyroid domain. Compared to controls, thyroid volume, thyroid functional capacity (SPINA-GT) and deiodinase activity (SPINA-GD) were significantly reduced in the RIT group.Conclusion Patients with subclinical hyperthyroidism improve both biochemically and in their QoL after RIT, compared to controls. QoL assessment should have a wider role in clinical practice to complement biochemical tests and help with treatment decisions.
Keywords: subclinical hyperthyroidism; quality of live; radioiodine treatment; prospective study